Modification of stainless steel fiber felt via in situ self-growth by electrochemical induction as a robust catalysis electrode for oxygen evolution reaction. (13th January 2020) - Zhu, Silu; Chang, Cuiping; Sun, Yanzhi; Duan, Guoyi; Chen, Yongmei; Pan, Junqing; Tang, Yang; Wan, Pingyu
Abstract: The development of cost-effective, highly efficient and robust electrodes for oxygen evolution reaction (OER) is greatly significant for water-electrolysis to produce hydrogen. In this paper, we report a stainless steel fiber felt (SSF) electrode with greatly enhanced OER catalytic performance and durability. The SSF is directly treated by cyclic voltammetry (CV) method in alkaline electrolyte, which is more facile and convenient than the traditional measures. The characterization results of X-ray diffraction, X-ray photoelectron spectroscopy and scanning electron microscopy indicate that an ultra-thin layer composed of Fe/Ni/Cr hydroxides/oxides with 3D open nanoporous structure is formed on the surface of SSF after CV treatment. The electrochemical tests show that the prepared SSF electrode displays a very low overpotential of 230 mV at 10 mA cm −2, a small Tafel slope of 44 mV dec −1 and good long-term durability of 550 h in 1 M KOH. The excellent OER performance of SSF electrode is contributed to the formation of hybrid metal hydroxides/oxides on its surface via in situ self-growth by electrochemical induction. Furthermore, the electrode only requires an overpotential of 340 mV at 10 mA cm −2 in 0.5 M Na2 CO3 /NaHCO3 solution. It is expectable that the modified SSF will be a promising catalysis electrode for water-electrolysis in large-scale commercial production. Highlights: Stainless steel fiber felt with large specific surface is modified as OER catalyst. The CV treating method is fast, simple and convenient. Ultra-thin Fe/Ni/Cr hydroxides with 3D nanoporous structure is formed after CV. The modified electrode has excellent catalytic performance for OER. The as-prepared electrode has superior long-term stability for about 550 h.